2016
DOI: 10.1007/s00381-016-3214-z
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial undifferentiated malign neuroglial tumor in Smith-Lemli-Opitz syndrome: A theory of a possible predisposing factor for primary brain tumors via a case report

Abstract: According to current literature, our case is the first report on coexisting of SLOS and intracranial undifferentiated malignant neuroglial tumor. Common pathways like impaired sonic hedgehog (Shh) signaling pathway may be considered for pathogenesis of a probable link between SLOS and brain tumors in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Mutations in human HMGCS1 have not been associated with disease, but there are 8 congenital anomalies that occur as a consequence of mutations within other enzymes of the CSP. [5][6][7][8][9][10][11]13,51 These congenital anomalies are characterized by diverse phenotypes, 7,21,[51][52][53] and mutations in the zebrafish hmgcs1 gene mimic these disorders, resulting in a multiple congenital anomaly syndrome. Therefore, zebrafish with mutations in hmgcs1 have the potential to reveal novel cellular and molecular mechanisms underlying individual phenotypes across multiple genetic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in human HMGCS1 have not been associated with disease, but there are 8 congenital anomalies that occur as a consequence of mutations within other enzymes of the CSP. [5][6][7][8][9][10][11]13,51 These congenital anomalies are characterized by diverse phenotypes, 7,21,[51][52][53] and mutations in the zebrafish hmgcs1 gene mimic these disorders, resulting in a multiple congenital anomaly syndrome. Therefore, zebrafish with mutations in hmgcs1 have the potential to reveal novel cellular and molecular mechanisms underlying individual phenotypes across multiple genetic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that cholesterol and isoprenoids regulate erythropoiesis using a zebrafish harboring mutations in the hmgcs1 gene (Vu57 allele). Mutations in human HMGCS1 have not been associated with disease, but there are 8 congenital anomalies that occur as a consequence of mutations within other enzymes of the CSP [5][6][7][8][9][10][11]13,48 . These congenital anomalies are characterized by diverse phenotypes 7,21,[48][49][50] and mutations in the zebrafish hmgcs1 gene mimics these disorders resulting in a multiple congenital anomaly syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Brain malignancy in individuals with SLOS has been reported in two cases (Oslejskova et al, ; Aslan et al, ), although biochemical or molecular confirmation for the diagnosis of SLOS was not provided in the latter reference. Both groups suggested dysregulation of the Sonic hedgehog (Shh) signaling pathway to be the potential underlying tumorigenesis mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Other reviews of brain tissues from individuals with SLOS revealed poor development of the corpus callosum, disordered arrangements of cellular layers in the cerebellum, and abnormal development of cerebral gyri (Cherstvoy et al, ; Curry et al, ). Malignant brain lesions in individuals with SLOS have been reported in two cases (Oslejskova et al, ; Aslan, Borcek, Pamukcuoglu, & Baykaner, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation